Apolipoproteins in fish: From lipid transport to innate immunity - SAHOO, P K; MOHAPATRA, AMRUTA; JENA, J K (The Indian Journal of Animal Sciences, 2017)
The fish has a strong innate immune system, and antimicrobial peptides play a major role in fish innate immunity, providing potential defence against broad spectrum of fish pathogens. Apolipoproteins,that are abundant proteins of plasma, playing important role in lipid transport and metabolism, also have potential antimicrobial activity. The resent review describes the classes, structural details and important biological functions of apolipoproteins reported in both mammals and fish with an emphasis on their roles in host defence. The role of fish apolipoprotein A-I, a major component of high-density lipoproteins (HDL), is described in great detail using different infection models along with its bactericidal and immunomodulatory activities in various fish species against wide range of fish pathogens.Further, role of some novel fish-specific apolipoproteins, including the mammalian ones, have also been defined with a special focus on the molecules described in Indian carp species. As the understanding on major apolipoproteins is limited in fish species, this review might serve as a foundation to explore further their functional diversity in Indian fish species.